استقرار الوطن الاجتماعي في ضوء الحديث النبوي - Abdul Saboor Abu Bakr (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
There is no good unless the Prophet guided his nation to him, and there is no evil unless the Prophet warned his nation against it. Islamic social values are characterized by being divine, eternal, realistic, balanced and comprehensive. And that commitment to the principles of Islamic law and social values of the Prophet, and their application on the ground has a prominent impact on achieving societal stability. There are many hadiths of the Prophet to regulate one's relationship with one's society, and among the fixed social values that the Prophet was guided to: social justice and honesty, dreaming and forgiveness, honesty, the necessity of kindness, the fulfillment of the covenant, and altruism.Among the social relations that the Prophet urged Allah to strengthen are: the man's relationship with his relatives and relatives, with the Muslim and others, with his neighbor and his slave, the relationship of the husband with his wife, the convict with his ruler and the young with the elder.One of the most important social etiquette that ensures the stability of the social homeland is to love for one's brother what he loves for himself, to command good and forbid evil, to cooperate in righteousness and piety, and to accompany justice and fairness.In order to ensure the stability of the social homeland, social problems such as theft, envy, backbiting and development, injustice, adultery, treachery, betrayal, fanaticism, arrogance, ridicule and the like must be eliminated.